Teaching The Holocaust As A Lesson In Remembering And Saying "No" To Hate: A Testimonial - Alsip, Emily (Teaching History: A Journal of Methods, 2002)
After age twelve, I could never eat pizza from Pizza Hut again. Let me explain. My mother regularly volunteered to accompany elderly people in our community on errands or to doctor appointments or on visits to similarly aged friends. I tagged along on one of these journeys and met a woman whose name I do not remember, despite the impression she left on my life. She was old, ancient looking to a twelve-year-old, and she talked slowly and with an accent. We were picking her up from a doctor’s office and taking her home to her small apartment.